Diagnosis and possible phylogenetic relationships of Psorophora (Grabhamia) dimidiata (Diptera: Culicidae) - Stein, Marina (2022)
Of the 16 species of genus Psorophora, subgenus Grabhamia, five occur in Argentina: Ps. cingulata, Ps. confinnis, Ps. dimidiata, Ps. paulli and Ps. varinervis. All life stages (except the egg) of the five species from Argentina, except Ps. dimidiata, are currently described. Therefore, the purpose of this work was to provide a complete description of all life stages, except the egg, and diagnosis to aid unambiguous recognition of the species. A total of 16 larvae were collected from natural habitats in Chaco, La Rioja and San Luis provinces and individually reared to obtain adults. Female Ps. dimidiata differs from other species of subgenus Grabhamia as follows: light brown scales on all veins, with some white scales only at base of C, 1A and along Sc, not forming pattern of spots, in some specimens white scales occur in short strip near base of Sc; all femora with well-defined subapical rings of white scales; proboscis without ring of white scales, white scales only on ventral surface; larval siphon widened at middle (not widened in Ps. paulli, Ps. varinervis and Ps. discolor (Coquillet)); 10–12 comb scales (all others less than 10). Psorophora dimidiata has the femur of all legs with a subapical ring of white scales. This ring is absent in other genera, although it is similar to the preapical band of pale scales present in the genus Coquillettidia (Mansoniini). The presence of a ring of white scales on the proboscis is indicated as a unique character for species of subgenus Grabhamia, however the proboscis of Ps. dimidiata does not have a ring of white scales. An interesting character is bidentate or bifurcated palatal papillae observed in Ps. dimidiata that are not mentioned in any of Psorophora species, nevertheless it was observed to be characteristic of Opifex fuscus Hutton. Based on the morphological characteristics mainly in the adult female of Ps. dimidiata, and considering the phylogenetic relationships found by other authors, we believe that this species could be placed in a basal position within Grabhamia, although a clear relationship with the rest of the species of the subgenus is not yet possible to establish. Studies based on molecular analysis would strengthen or reject this hypothesis.